Konstruksi Laki-Laki Ideal dalam Iklan Skincare Pemutih: Kajian Bahasa, Visual, dan Narasi di Media Sosial - Djokowidodo, Agustinus; Bintoro, Putri (Prodi Sastra Indonesia, FKIP Universitas Jambi, 2026)
The increasing phenomenon of men using skincare in the digital era indicates a shift in masculinity values, previously associated with physical toughness, toward aesthetics, self-care, and visual performativity. Whitening skincare advertisements on social media, particularly TikTok, play a significant role in constructing the ideal male: a man with bright, clean, athletic, and professional skin. This study aims to uncover how the language, visuals, and narratives of advertisements construct representations of modern masculinity through Fairclough's critical discourse analysis. The research method uses a qualitative approach, collecting data in the form of six whitening skincare advertisements for men, which are then analyzed across three dimensions: text, discursive practices, and socio-cultural practices. The results show that at the textual level, advertisements employ motivational and heroic lexicons, such as dare to win it, fresh & clean, and